Optimizing The Implementation of Tank Coolingdown to Prepare For The LNG Loading Process on LNG Carrier Pan Africa Ships - Dzaky, Muhammad Ahyar; Sutoyo; Kusumawati, Elly; Nur Prasetyo, Anugrah (Journal of Engineering Science and Technology Management, 2026)
LNG cargo tanks are specifically designed to transport liquefied gas, and the coolingdown process becomes a critical stage prior to loading. This process is performed by spraying liquid gas through spray nozzles installed on the tank dome. This study employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, which consist of data condensation, data display, and conclusion drawing. The findings indicate that the coolingdown process on LNG/C Pan Africa generally complies with SIGTTO and IGC Code standards. However, two major issues were identified: a leakage in the cooldown valve on loading line number 2 caused by corrosion, which reduced the cooling rate from the standard 20°C/hour to approximately 10°C/hour, and a 1.5 hour delay in operating nitrogen system, which resulted in the IBS pressure not reaching the required 0.2-0.4 kPa. The study concludes that optimization of the coolingdown process can be achieved through preventive maintenance of the cooldown valve, improved coordination among officers, and enchanced accuracy in monitoring temperature and pressure. These recommendations are expected to improve the efficiency and safety pf LNG loading operations.